2010
DOI: 10.3109/03639045.2010.495751
|View full text |Cite
|
Sign up to set email alerts
|

Design of optimized diffusion-controlled transdermal drug delivery systems

Abstract: The proposed design is almost universally applicable and satisfies therapeutically relevant specifications while maximizing drug utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It was determined that spatial variation of an API can significantly influence its release and provide improved performance compared with a monolithic DIA when distributed appropriately (46). Nauman et al further expanded this idea by creating a model that can predict optimal patch design configuration for a single drug that is distributed in a bilayer based on minimizing the burst effect and maximizing drug depletion to increase patch efficiency (47). Both authors concluded that increased drug loading within the second layer increases controlled release and decreases burst effect.…”
Section: Altered Patch Design With Maintained Composition Altered Drug Permeation Of Each Apimentioning
confidence: 99%
“…It was determined that spatial variation of an API can significantly influence its release and provide improved performance compared with a monolithic DIA when distributed appropriately (46). Nauman et al further expanded this idea by creating a model that can predict optimal patch design configuration for a single drug that is distributed in a bilayer based on minimizing the burst effect and maximizing drug depletion to increase patch efficiency (47). Both authors concluded that increased drug loading within the second layer increases controlled release and decreases burst effect.…”
Section: Altered Patch Design With Maintained Composition Altered Drug Permeation Of Each Apimentioning
confidence: 99%
“…Traditionally, the skin, the SC and the diffusion phenomena have been studied associated with pure mathematical models, especially based on the Fick Equation [24][25][26][27][28][29][30][31][32]. A systematic analysis of these models implies a division based upon the particular approach and use of the Fick Law.…”
Section: Dermic Diffusion and Mathematical Models: A Reviewmentioning
confidence: 99%